A model of entrepreneurship education in franchising – application of outside-in marketing with a behavioural focus. Issue 1 (25th September 2019) - Quach, Sara; Weaven, Scott; Thaichon, Park; Grace, Debra; Frazer, Lorelle
Abstract : Purpose: Drawing on an outside-in marketing perspective, this paper aims to outline the development, implementation, evaluation and reflection of a real-world entrepreneurship education (EE) intervention with cognitive, affective and ultimately behavioural objectives. Design/methodology/approach: A specific and uniform EE program specifically targeted to current "would be" entrepreneurs who were investigating the franchising business model was developed, focusing on the behavioural outcomes. The effectiveness of the EE intervention was evaluated using a quasi-experimental research design, which involved franchisees who had not participated in the EE intervention (control group) and franchisees who had participated in the EE intervention (experimental group). The administration of the national on-line survey yielded a total of 520 responses (194 in the experimental group and 326 in the control group). Findings: The planning process in the pre-intervention stage included situation analysis, objective setting and decisions in relation to the communication strategy, i.e. content and mode. The effectiveness of the EE intervention was evaluated in the post-intervention stage. The findings indicate that EE intervention resulted in participants' positive cognitive, affective and behavioural outcomes such as performance and relationship management. Finally, following a reflection process, additional elements covering topics related to work-life balance were incorporated into the module pertaining to an individual's suitability to become a franchisee. Originality/value: This paper proposes a conceptual framework that represents an outside-in EE approach whereby problems, audiences, objectives and communication strategies (content and method) are strategically intertwined to produce relevant, measurable and diagnostic behavioural outcomes. The EE intervention can also improve the B2B relationship between actors in a business network.